Prevalence of Cryptococcal Antigenemia and Associated Factors among HIV/AIDS Patients at Felege-Hiwot Referral Hospital, Bahir Dar, Northwest Ethiopia - Mohabaw Jemal; Teshiwal Deress; Teshome Belachew; Yesuf Adem (International Journal of Microbiology)
Background. Cryptococcosis is the most common opportunistic fungal infection. High morbidity and mortality are frequently observed among hospitalized HIV/AIDS patients, particularly having CD4 count ≤100 cells/μl. Therefore, this study aimed to determine the prevalence of cryptococcal antigenemia and associated factors among HIV/AIDS patients. Methods. A hospital-based cross-sectional study was conducted among 140 HIV/AIDS patients. A cryptococcal antigen test was performed for all patients along with medical chart and laboratory registration book review. Cryptococcal antigen was detected from serum by using Remel Cryptococcal Antigen Test Kit. Data related to possible associated factors were extracted from patients’ charts and laboratory registration book. Data were coded, entered, and analyzed using SPSS version 20. Logistic regression analysis was done to see the association between dependent and independent variables. A P value <0.05 was considered statistically significant. Finally, data were presented in the form of texts, figures, and tables. Result. Among 140 serum cryptococcal antigenemia-tested study subjects, 16 (11.43%) were positive for serum cryptococcal antigen. Of them, 43.8% (7/16) were pulmonary tuberculosis coinfected, 31.2% (5/16) were extrapulmonary tuberculosis positive, and 25% (4/16) had bacterial bloodstream infections. In addition, 68.7% (11/16) had CD4 count less than 100 cells/μl, 18.7% (3/16) had CD4 count 100–150 cells/μl, 50% (8/16) were antiretroviral therapy defaulters, and 31.3% (5/16) were naïve. In this study, the majority, 75% (12/16), of the serum cryptococcal antigen-positive subjects were clinical stage IV. Of the assessed associated factors, tuberculosis coinfection (AOR: 0.04; 95% CI [0.005–0.25]) and antiretroviral therapy status (AOR: 0.02; 95% CI [0.001–0.5]) were significantly associated factors enhancing serum cryptococcal antigenemia. Conclusion. In this study, the high rate of cryptococcal antigenemia was observed among hospitalized HIV/AIDS patients, and it is alarming and highlights the need for improving CD4 status, expanding serum cryptococcal antigen screening, and strengthening regular cryptococcal antigenemia surveillance systems.